Relative income position and happiness: Are cabinet supporters different from others in Japan? - Eiji Yamamura; Yoshiro Tsutsui; Fumio Ohtake (Osaka University, Institute of Social and Economic Research (ISER), 2015)
During the period of 2001-2006, the Liberal Democratic Party (LDP) adopted a market-oriented policy under the Koizumi cabinet. In 2006, following the formation of the first Abe cabinet, the LDP returned to a traditional redistributive policy. We assume that the supporters of the Koizumi cabinet had an expectation of upward income mobility via the market. On this assumption, using data covering the Koizumi and first Abe cabinets, this paper attempts to examine whether the effects of relative income differ between supporters and non-supporters of the Koizumi cabinet. Key findings are as follows: within the Koizumi cabinet period, a relatively low-income position is negatively related to happiness for non-LDP supporters but not for LDP supporters. However, under the period of the first Abe cabinet, the difference in the effect of relative income for LDP supporters and others disappears. These results imply that an expectation of market outcomes leads to a difference in the effect of relative income position on happiness levels. Namely, during the Koizumi cabinet period, low-income supporters believed that their income position would improve under Koizumi's market-oriented policy, and during the Abe cabinet period, low-income LDP supporters, like non-supporters, did not hold such an optimistic view.
Keywords: I31; D72; 330; Relative income; Positional concerns; Happiness; Government supporter; Japan